Analysis of Employee Mental Workload Using The NASA-TLX Method (Case Study at PT. ABC) - Reza Saputra; Nana Rahdiana; Karnadi Karnadi (Universitas Islam Raden Rahmat, Malang, 2025)
Human resources are the most important assets for a company. Each worker has their own role and obligations which will result in their own workload. PT. ABC is one of the companies that provides surface finishing services, electroplating services and electrode position painting. From the observation results, there are complaints about insufficient time adjustments to meet targets and demands from superiors for these targets, resulting in increased mental workload. In order to overcome this problem, it is necessary to measure the mental workload felt by employees using the NASA-TLX method, this method measures 6 dimensions of workload including Mental Demand, Physical Demand, Temporal Demand, Performance, Effort and Frustration Level. This study shows the acquisition of workload scores, it is known that 75% of employees have a high category workload and 25% of employees have a very high category workload. The dominant aspects that cause the amount of mental workload of PT.ABC employees are Mental Demand of 19.62%, Effort of 19.40% and Physical Demand of 17.93%. In order to minimize the level of mental workload, namely by adding some workers in the production and quality control sectors.